Overview Sociology of Law and Positive Law to Diversion Internal Joint Property Marriage - Wafa’ Zenassa’dy; Rahayu Hartini (JIL : Journal of Indonesian Law, 2023)
Study this background because many case shape transition right on treasure together no involve from one party good party husband nor wife . circumstances above give birth to problem law new that is related with how view sociology laws and regulations applicable law to diversion treasure together in marriage so creation justice in society . Diversion treasure together according to Article 35 paragraph (1) Constitution Number 1 year 1974, husband or wife could Act on agreement second split party . By therefore if wrong one party divert treasure together must with agreement or permission from husband nor wife especially first . Purpose from study he hoped Public capable implementing the transition process treasure together corresponding with Applicable law . Study this use method study qualitative through studies References or library research . With using primary data in the form of Applicable laws and cases similar to what happens in the environment society .